Analisa Perbandingan Yamamoto Recursive Code Dan Elias Gamma Code Dalam Kompresi File Teks - Tegar Syah Pratama (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The development of increasingly advanced technology and the increasing number of computer users causes a data explosion and data transfer from one device to another. There are various types of multimedia data that can be loaded, namely text, images, audio (sound, sound, music) and video. The data is generally compressed first so that the exchange process does not take too long. Many things have been done to overcome this, one way is to reduce the size of the files stored by using file compression techniques. There are many algorithms that have been used to compress files, 2 of which are Yamamoto Recursive Code and Elias Gamma Code. So that the comparison process of the two algorithms will be carried out by determining the parameters, namely Ratio Of Compression (RC), Compression Ratio (RC), Redurancy (RD), and Space Saving (SS). Based on the calculation results, the results of the Yamamoto Recursive Code algorithm performance measurement can compress text files by 85%. Meanwhile, the performance of the Elias Gamma Code Algorithm can compress text files by "60,62%." So it can be concluded that the Elias Gamma Code algorithm is better at compressing text files.